Selection and assessment of filtration-capacitive parameters for clay reservoirs - Ramiz Aliyevich Gasumov (Наука. Инновации. Технологии)
Consideration is given to the selection and assessment of filter-capacitive parameters of clay reservoirs, substantiation of oil-gas-saturated thickness and permeability of reservoirs. The results of studies containing information on the various properties of clay rocks in Lower Maikop deposits are presented: porosity; volume weight; calcification; coefficient of hydro-phobicity characterizing the physical and chemical properties of surface; specific electric resistance; interval time of propagation for elastic longitudinal waves. In accordance with the features of natural reservoir structure, taking into account the results of drilled wells, according to their location, three categories of plots for carrying out prospecting work are identified. The approaches are described according to the data of hydrodynamic studies, the possibility of determining the numerical values of the parameters characterizing the hydrodynamic properties of wells and formations, and also the features of their structure (heterogeneity, impermeable boundaries) are determined. The results of hydrodynamic well studies were selected and the indicator diagrams were studied to quantify the parameters of reservoir; the pressure recovery curves recorded have an appearance typical for fracture-pore type reservoir.